A CONCEPTUAL STUDY ON BHAJAN INTERPRETATION BASED ON ‘BHAJAN SAMRAT’ PADMASHREE DR. ANUP JALOTA’S POINT OF VIEW - Ghosh, Manali; Majumdar, Manasi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
‘Bhajan’ is a Devotional Music genre in India. It is in practice as rituals in India for worshipping God or for God Realization or self-realization. Apart from that, Bhajan is extensively found to be sung in different way, different styles by different singers. Some general concepts are there in the society about the interpretation of Bhajan. This study aims to bring and highlight the details of the interpretational style of Bhajan singing of Bhajan Maestro Anup Jalota who is often addressed as the ‘Bhajan Samrat’. In this article, after the introductory part, I have discussed the reviews of Anup Jalota’s interviews where he had talked about the Bhajan interpretational style, his views and other knowledge about Bhajan and a little bit about how he maintains it musically. The interpretation of the existing data rose up a number of questions those where supposed to be answered. Then those questions have been answered by the legend himself in an interview taken by myself, the author. The overall concept about his views has been found at the conclusion. Since, gaining knowledge about the style of Bhajan interpretation has been the ‘aim’ of my doctoral thesis paper, this study is done in order to bring a strong boost to my thesis topic, as well as it’s inspired by my thesis.